Elephant grass silage with the addition of crambe bran conjugated to different specific mass - Arilson Moraes Cardoso; Saulo Alberto do Carmo Araújo; Norberto Silva Rocha; Felipe Nogueira Domingues; Jorge Cardoso de Azevedo; Lilian de Araújo Pantoja (Acta Scientiarum. Animal Sciences, 2016)
This study aimed to evaluate the effects of inclusion of crambe bran concentrations (Crambe abyssinica Hochst.) with different specific masses in elephant grass silage (Penninsetum purpureum Schum.). For that, the bromatological and microbiological compositions of the experimental silages were determined. We used 48 mini silos distributed in a completely randomized design, arranged in a factorial 4 × 3, four levels of inclusion of crambe bran (0; 10; 20 and 30%) and three specific masses (400; 500 and 600 kg MN m-3), with four replications. After 240 days of fermentation the silos were opened. It was observed linear effect on DM, CP, NDFap, ADFap, HEM, LIG, NFC, TC and population of bacteria that produce lactic acid with the addition of crambe meal. There was interaction between the crambe bran factors and specific masses on the values of pH and N-NH3. For MM variables and yeast count there was a negative linear effect due to the evaluated specific mass. The inclusion of crambe bran helps to increase the fermentative profile and the bromatological composition of elephant grass silages studied, and the best results were obtained with the addition of 30% of this coproduct, based on the natural matter.